STRATEGI GURU DALAM MENGEMBANGKAN KETERAMPILAN MENULIS DAN LITERASI ISLAMI SISWA DI TADIKA ANAKKU SHOLEH - Fauziah Sinaga, Silvi; Mavianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe teacher strategies in developing writing skills and Islamic literacy for students aged 5–6 years at Tadika Anakku Sholeh, Selangor, Malaysia. A qualitative descriptive approach was employed with data collected through observation of 12 learning sessions, in-depth interviews with the principal and three classroom teachers, and documentation analysis of 15 students' writing products. Data were analyzed using Miles and Huberman's interactive model. Findings reveal that teachers consistently applied basic Islamic writing strategies hijaiyah letters, Islamic words (Allah SWT, Prophet), and daily prayers with 100% frequency. However, creative strategies such as game-based writing and copying short verses were only implemented by 33% of teachers, indicating varying adaptive capacities. Students' writing skills achieved "good" category (average 3.13/4.00) for letter formation, word writing, and accuracy, while neatness remained at "fair-good" level (2.80) due to fine motor development limitations. Supporting factors included the Islamic school environment, teacher creativity in utilizing simple media (sand, flour), and management support. Hindering factors comprised limited variety of Islamic writing media, minimal teacher training, and diverse parental expectations. The study concludes that teacher strategies represent creative adaptation where teacher resilience compensates for infrastructure and training limitations in early childhood Islamic literacy development.